Management of Cocoa Black Pod Disease by Farmers in Edo State, Nigeria: The Role of Farmer Field School - Okeoghene , Ebewore Solomon (Asian Journal of Agriculture and Rural Development, 2020)
The specific objectives of the study were to find the contribution of FFS training in control of the disease; examine the role of FFS in improving farmers’ competency in management of black pod disease, and determine the proportion of farmers that benefited from FFS training on management of black pod disease. A multi-stage sampling procedure was employed in selecting 76 FFS farmers and 74 other farmers, and various descriptive statistics and t-tests were used to analyze data. The results showed that FFS played a major role in improving FFS farmers’ competency in the management of black pod disease. The t-tests conducted showed significant differences in knowledge between FFS farmers and other farmers.